"MY FIRST PAINTING”: ANALYSIS OF EXPRESSIVE IMAGES OF KINDERGARTEN STUDENTS IN BULELENG SUBDISTRICT, BALI" - Luh Suartini (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
This article aims to analyze the first images of kindergarten students in Buleleng district. This article uses interpretive qualitative methods with the theory of art education, especially the development of children's art as formulated by Viktor L. Article comes to the discussion of visual elements and interpretive meanings. The visual element consists of the repetition of shapes, the painting of flat spaces, and the painting of stacked spaces. Interpretively the theme of these children's paintings is my home, and my surroundings. It can be concluded that this article1, the use of lines as the basis of geometry to give the impression of objects. 2, do not yet have space awareness. 3, interpretively the theme of the children's paintings of myself, my home, and my surroundings Keywords, my first painting, kindergarten student, Buleleng.